2009
DOI: 10.1093/ejechocard/jep026
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular anatomical and functional changes with ageing in type 2 diabetic adults

Abstract: Type 2 diabetic patients demonstrate an early and concomitant induction of systolic and diastolic myocardial dysfunction as a preclinical manifestation of diabetic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…Such alterations lead to cardiomyocyte necrosis and apoptosis associated with fibrosis and subsequent myocardial dysfunction, which is called diabetic cardiomyopathy (33). At an early stage, US techniques for myocardial strain assessment such as tissue Doppler imaging (22,(34)(35)(36)(37)(38) and speckle tracking imaging (23)(24)(25) help show decreases in systolic function in DM patients without patent cardiomyopathy, compared with that in normoglycemic patients. Because of technical issues, longitudinal dysfunction (22,(34)(35)(36)(37)(38) has been well validated by using US techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alterations lead to cardiomyocyte necrosis and apoptosis associated with fibrosis and subsequent myocardial dysfunction, which is called diabetic cardiomyopathy (33). At an early stage, US techniques for myocardial strain assessment such as tissue Doppler imaging (22,(34)(35)(36)(37)(38) and speckle tracking imaging (23)(24)(25) help show decreases in systolic function in DM patients without patent cardiomyopathy, compared with that in normoglycemic patients. Because of technical issues, longitudinal dysfunction (22,(34)(35)(36)(37)(38) has been well validated by using US techniques.…”
Section: Discussionmentioning
confidence: 99%
“…At an early stage, US techniques for myocardial strain assessment such as tissue Doppler imaging (22,(34)(35)(36)(37)(38) and speckle tracking imaging (23)(24)(25) help show decreases in systolic function in DM patients without patent cardiomyopathy, compared with that in normoglycemic patients. Because of technical issues, longitudinal dysfunction (22,(34)(35)(36)(37)(38) has been well validated by using US techniques. In comparison, the importance of radial dysfunction is more controversial (24,25,34,35), but circumferential function is largely unexplored, with only preliminary and conflicting data (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of recent echocardiographic techniques, there is emerging evidence of subtle abnormalities in long-axis systolic function in these patients. [4][5][6][7] Our results showed that patients with diabetic microvascular complications had a decreased longitudinal average isovolumic contraction acceleration not only at the mitral annulus but also at the 3 levels of the LV wall, which showed the presence of global and regional systolic dysfunction in the long-axis direction. In addition, patients without diabetic microvascular complications had regional longitudinal systolic dysfunction, although the global LV longitudinal contractility was normal.…”
Section: Left Ventricular Systolic Dysfunctionmentioning
confidence: 56%
“…[4][5][6][7] However, only a few studies have been performed regarding radial systolic function, and data about the changes in radial systolic function in diabetic patients are still controversial. [7][8][9] Conventional echocardiography is not sensitive enough to detect subtle changes in radial contractility.…”
mentioning
confidence: 99%
See 1 more Smart Citation